Effect of Ignition Timing on Fuel Consumption and Emissions of a Dual Chamber Spark Ignition Engine - Rangkuti, Ch. (Universiti Putra Malaysia Press, 2000)
Fuel consumption and emissions from a dual chamber, stratified charge, spark ignition engine with different ignition timing were investigated. Retarded ignition, relative to MBT timing, yielded poorer fuel consumption, especially with lean mixtures. The poorer combustion associated with the late burning did not result in increased UHC emissions - these in fact is reduced. Emissions of CO were higher (for lean mixtures); NOx levels were much the same at wide-open and 65% throttle settings and significantly lower at the 40% throttle setting.